PENINGKATAN KOMPETENSI BAHASA INGGRIS DI PESANTREN AL MASHDUQI MELALUI PERMAINAN TRADISIONAL TEBAK KATA - Zulkhaeriyah Zulkhaeriyah; Fitriyatuz Zakiyah; Muhammad Masqotul Imam Romdloni Imam; Luthfi Awwaliyah Luthfi Awwaliyah (JCS, 2023)
This research is motivated by the low English proficiency of new students at one of pesantren in Bangkalan Madura, namely pesantren Al Mashduqi. The low English proficiency of the students is indicated by the low interest of the new students to take part in English club activities. In addition, based on the results of the pre-test, the students who were new students at Universitas Trunojoyo from various majors had difficulty identifying the parts of speech in an English sentence. The purpose of this research is to find out the effectiveness of traditional game, namely Guessing words in improving the English competence of Students in pesantren Al Mashduqi. The authors, who are English lecturers, work closely with the pesantren’s leader to conduct training in order to improve English competence of new students at the pesantren. By collaborating lecture and game’s methods, this training is divided into several stages. Those are pre-test, giving material of part of speech, implementing the game, and post-test. Based on the results of the comparative evaluation of the pre-test and post-test, the traditional game, namely word guessing is able to help students in understanding English material, in this case part of speech, easily and fun